Hubungan Antara CT Value dengan Faktor Determinan pada Pasien COVID-19 dengan Ventilator di RSPAD Gatot Soebroto - Hendik Wicaksono (Jurnal Riset Hesti Medan, 2022)
Indonesia has confirmed 1,528 cases of COVID-19 with 136 deaths. The number of cases as of May 20 2020 was 4,806,299 people and caused 318,599 deaths worldwide. SARS-CoV-2 and SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV) cause severe pneumonia with mortality rates of 2.9%, 9.6% and 36%, respectively. The design or research design used is descriptive with a cross-sectional approach (cross-sectional study). Data collection in this study used secondary data in the form of hospital medical records from July to September 2021. Most of the 41 male respondents, 25 (61%) had strong positive CT and the remaining 16 (39%) have a weak/moderate positive CT. There were 35 female respondents, 23 people (65.7%) of whom were strong positive CT and the remaining 12 people (34.3%) were weak/moderate positive CT. The statistical test results with Chie Square obtained a greater P value of 0.851 and a 0.05 so that it can be concluded that there is no relationship between gender and the CT category. Age characteristics in this study were adult respondents (20-60 years) in Covid-19 patients with ventilators, reaching 46 people or identical to 60.5% of the sample population and male gender respondents dominated than women, which reached 53, 9% or 41 people out of a total population of 76. Investigations for Covid-19 patients on ventilators for abnormal D-dimer characteristics (500 ng/ml) totaled 72 respondents or reached 94.7%. In the statistical test with the results of the respondent's correlation test between the CT category and the risk factors for Covid-19 (age, sex, comorbid factors except DM comorbid factors), and the results of supporting examinations (Ddimer, chest photo), and mortality rate, it can be explained that only DM comorbidity has a relationship with the CT category, while age, gender, hypertension comorbidity, obesity comorbidity, and cardiovascular disease comorbidity, as well as mortality rate, do not have a relationship with the CT category.